Temporal and altitudinal variations in benthic macroinvertebrate assemblages in an Andean river basin of Argentina - Scheibler, Erica Elizabeth (2014)
Environmental variables and benthic macroinvertebrate assemblages were spatially and seasonally examined over two consecutive years (2000-2002) along a glacier and snowmelt river in the central-west of Argentina where lies the highest peak in America, Mount Aconcagua (6956 m elevation). The goal was to assess seasonal and altitudinal variability in benthic community structure and to define whether physical-chemical variables affect distribution of aquatic insects. The Mendoza River Basin was characterised by high variability in flow and transparency, high conductivity, hard calcium sulphate water, neutral and alkaline pH, and dominant substrate composed of small blocks, cobbles, pebbles, and sand-silt. Richness of invertebrates was low, with the lowest taxonomic richness being recorded at the mouth. The dominant group with highest taxonomic richness was Diptera, although caddisflies, mayflies, beetles, and stoneflies were present. Seasonal and spatial variations in biotic and abiotic variables were detected. Maximal densities and taxonomic richness were recorded in autumn and winter. From Modified Morisita?s Cluster analysis it was found that the system is divided into two groupings of sites related to each other by faunal composition. INDVAL revealed species turnover along the altitudinal gradient of some taxa: Andesiops, Massartellopsis, Edwarsina, Chelifera, and Ceratopogonidae had preference for the headwaters (2835-2425 m elevation), Smicridea murina and Baetodes for the lower section (1413-1085 m elevation), and Austrelmis for the middle and lower sections. The middle section (1846-1727 m elevation) was a transition area where taxa from the headwaters and the lower section coexisted. Generalised Linear Models evidenced that altitude was the major factor determining macroinvertebrate assemblages along the large arid Mendoza River and that the physical-chemical variables that most influenced variation in community structure were: transparency, bicarbonate concentration, pH and substrate type. Our results suggest that benthic macroinvertebrate structure and environmental variables are affected in different ways by seasonal and altitudinal variations.